Al-Taghayyurāt al-Ṣawtīyyah bayna al-Lughatayn al-ʻArabīyyah wa al-Tāmiliyyah: Dirāsah Taqābuliyyah - Sithy Shathifa, Mohammed Cassim; Ali, Asem Shehadeh (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2024)
Sounds affect each other. It brings to change one of the sounds. The phonological changes that occur as a result of the influence of sounds on some of them are; assimilation, dissimilation, and replacement. The question "Are there similarities in phonological changes between Tamil and Arabic languages which are from two different language families" is the research problem. Thus, this research aims to identify the similarities and differences in phonological changes among them. This research uses contrastive methodology under the descriptive analysis to find out the similarities and differences among them. Secondary data were collected from books, research and previous studies. At the end of the study, the researchers concluded that the phenomenon of assimilation in the Arabic language often exists between the sounds of a single word, while in the Tamil language this phenomenon occurs between the two words when they are linked to create a new word from them. It is divided into several in the two languages in terms of the characteristics of the sounds, and in terms of the degree of effect, place, and the relationship between the influencer and the affected; among them, assimilation of Arabic consonant is divided into six types, such as complete, partial, contiguous, non-contiguous, progressive and regressive. There are five types in the Tamil language, such as progressive, regressive, complete, contiguous, and non-contiguous. Assimilation of Tamil vowels is in three forms: assimilation of vowel with a vowel, assimilation of consonant with a vowel, assimilation of vowel with consonant while in the Arabic language it occurs in four forms: assimilation of vowel with a vowel, assimilation of semi-vowel with a vowel, assimilation of semi-vowel with a consonant, assimilation of vowel with a semi-vowel. When comparing the dissimilation in Arabic and Tamil, this term in both languages indicates one thing. It is the difference between the influenced sound and the one affecting it, in addition to the fact that it occurs in the Arabic language in a specific system and in specific cases. But no rules and order were followed for this phenomenon, nor were there any types for it in the Tamil language even though it exists in the Arabic language. Learners face many problems in identifying phonological changes without comparative knowledge of their mother tongue and adequate applications.